Preparation of silica supported nanoscale zero valence iron and its feasibility in viscosity reduction of heavy oil. (1st May 2014) - Yang, Zhancun; Liu, Xueliang; Li, Xiaohong; Zhao, Mengyun; Zhang, Zhijun; Su, Changming
Abstract : Conventional solvent and thermal enhanced oil recovery techniques are less competitive, because of the presence of resin and asphaltene components which are difficult to remove; therefore it is imperative to develop new types of catalysts for the efficient recovery of heavy oil. In this reported research, silica‐supported nanoscale zero valence iron (denoted as SiO2 /nanoFe) is adopted as a catalyst to break the C–S bonds of resin and asphaltenes so as to reduce the viscosity of heavy oils and acquire enhanced oil recovery. A target SiO2 /nanoFe catalyst was prepared via liquid‐phase reduction of ferric chloride hexahydrate by sodium borohydride in the presence of surface‐modified silica as a support. The as‐prepared SiO2 /nanoFe catalyst was characterised by transmission electron microscopy, X‐ray diffraction and Fourier transform infrared spectrometry. The dispersibility of as‐prepared SiO2 /nanoFe catalyst in various organic solvents was evaluated, and its specific surface area was determined using classic Brunauer‐Emmett‐Teller isotherm method. Moreover, the catalytic performance of the SiO2 /nanoFe catalyst for the aquathermolysis process of a heavy oil sample collected from Shengli Oilfield (Dongying, China) was evaluated. It was found that as‐prepared SiO2 /nanoFe, composed of silica with an average size of about 10 nm and zero valence iron nanoparticles with an average size of several nanometers, exhibits good anti‐oxidation stability. The SiO2 /nanoFe catalyst also exhibits good catalytic performance for the aquathermolysis process of heavy oils; in particular, at a mass fraction of 1.0%, it can significantly reduce the viscosity of a tested heavy oil from 184 to 42 Pa·s, showing promising potential in the industrial production of heavy oils.